Relationships between cognitive and affective of test anxiety with gender and academic achievement among cognitive science students - Nurfarahin, Mohd Idris (Universiti Malaysia Sarawak (UNIMAS), 2015)
The major aim of this quantitative study is to investigate the relationships between cognitive and affective of test anxiety with gender and academic achievement. This study also aims to determine which one of the two test anxiety factors is the most dominant factor that influences students' academic achievement. By employing random sampling technique, 206 respondents from second and third year undergraduate students of Cognitive Science Program (Session 112015/2016) were randomly selected. Questionnaires were distributed and the data obtained was then analysed by using both descriptive and inferential statistics analyses. The results showed that cognitive and affective factors of test anxiety were significantly correlated to students' academic achievement where (r = -.264, p < .01) and (r = -.314, p < .01) respectively. However, it was revealed that these two factors were not correlated to gender. Results also showed that affective factor (emotionality) contributed more in test anxiety than cognitive factor (worry), yet, the study found that variance of test anxiety affected students' academic achievement by only 9.9%. To conclude, test anxiety is one of the factors which are responsible for students' underachievement and low performance but it can be managed if the students know how to cope with test anxiety.